Construction and phenotypic classification of synthetic dual-pole Escherichia coli cells - Tsung-Wei Chou; Ing-Jen Huang; Ya-Chu Hsu; Szu-Hua Wu; Jui-Chung Hong; Yu-Hao Ko; Ting-Ran Su; Jie-Hong Roland Jiang; Hsiao-Chun Huang (Communications Biology)
Abstract Macromolecular complexes anchored at one cell pole have previously been utilized to achieve synthetic asymmetric cell division in Escherichia coli. In nature, however, robust asymmetric cell division often relies on gradients established between two opposing poles. Here, we present a second-generation synthetic genetic circuit that enables two distinct scaffolding proteins to localize at opposite poles in E. coli. By engineering a PodJ fragment as the second scaffold and integrating SpmX, a negative regulator of PodJ condensation, as a direct chimera with PopZ, we effectively confined PopZ and PodJ to opposite poles within E. coli. Additionally, we developed a neural network-based classification method to identify these synthetic dual-pole cells, further advancing the synthetic biology toolkit for programmable cell differentiation.